Koko's kitten - Patterson(3, (BFrancines (New York Scholastic, 1985)
The real life experience of Koko, a gorilla in California who uses sign language, with a young kitten whom she loved and grieved over when it died
Hurg
5
Keywords: Kittens -- Juvenile literature; Koko (Gorilla) -- Juvenile literature